Young rural women’s perspectives on the impact of education supported development projects on their lives: cases from Upper Egypt governorates - Hosny, Ola (AUC Knowledge Fountain, 2015)
Over the last years, young rural women’s vulnerability to the social and economic conditions became the focus of the literature (El Laithy, na). Current studies show that women’s capacities to participate in the development processes of their communities have been jammed with unequal gender, socio-economic and power relations (Kabeer, 2012). Yet, many development programs were designed and implemented to reach deprived women from different socio-economic backgrounds, educate or train them, build their capacities and prepare them to join the labor market and be active members inside their communities (USAID, 2013). This research study examines young rural women’s perspectives in Upper Egypt governorates on the impact of the education supported development projects on their lives, calling for an update of the state of knowledge of the effect of development projects on specific areas such as; women empowerment, gender equity, civil society enhancement and the integration of social stratification in underprivileged communities. The main findings explored in this study revealed the urgent need of placing the following changes inside the intervened communities; establishing social accountability, building social resilience, effecting scaffolding, resolving ideological debates and integrating projects’ social cohesion inside the villages’ communities. The study offers recommendations for educators, policy makers and practitioners who are concerned with education support development projects directed to young rural women in Egypt and other countries with similar contexts.